Solving the Problem of Synthesis of an Automatic Control System for a Distillation Column - Safarova, A.A. (Herald of Azerbaijan Engineering Academy, 2025)
The oil refining and petrochemical industries are considered to be the leading sectors of the national economy. The purpose of these facilities is to ensure the production of a wide range of high-quality petroleum products from crude oil. The requirements for quality indicators of various petroleum products produced at these technological facilities require the creation of more modern and advanced control systems. It should be noted that one of the main problems of control theory is the creation and development of new control systems capable of adequately responding to more dynamically changing external and internal stimuli for complex oil refining technological complexes in accordance with the requirements of the time. Therefore, it is relevant to create new automated control systems capable of providing the required accuracy of quality control.